Measured PM2.5 indoors and outdoors related to smoking prevalence by Zip code using 14,400 low-cost monitors in California, Washington, and Oregon - Lance Wallace (Indoor Environments)
Low-cost monitors have made possible for the first time measurements of long-term (months to years) potential indoor exposures to fine particles. Indoor and outdoor measurements made over nearly 5 years (2017–2021) by the largest network of low-cost monitors in the United States (PurpleAir) are compared to the prevalence of adult smokers in 1650 Zip codes within the three West Coast states of California, Oregon, and Washington. The results show that mean potential indoor exposures above the 75th percentile of adult smoking prevalence are more than 50 % higher than those below the 25th percentile. Mean outdoor concentrations are also elevated, but by a smaller amount (∼ 20 %). Both comparisons are significant at the p < 0.001 level. The elevation of PM2.5 concentrations with increasing smoking prevalence is evidence of environmental disparities in income, education, and other socioeconomic indices. The relatively stronger effect on indoor rather than outdoor PM2.5 exposures highlights the importance of including indoor measurements when possible in environmental justice studies.